Pemberdayaan Pelaku UMKM Desa melalui Digitalisasi Pembayaran : Implementasi QRIS dengan Metode Community Based Participatory Action Research di Desa Pematang Tengah, Kecamatan Tanjung Pura, Kabupaten Langkat - Mhd. Rofi Febrian; Atikah Humaidah Hasibuan; Muhammad Ardiansyah; Laylan Syafina (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a fundamental pillar of the Indonesian economy, but their potential is often hampered by the digital divide, especially in rural areas. The Quick Response Code Indonesian Standard (QRIS) initiative is a way for the government to encourage digital transformation and make payments more accessible to everyone. This article aims to document and analyse the process and impact of a community service programme that facilitated the adoption of QRIS among 10 MSMEs in Pematang Tengah Village, Tanjung Pura Sub-district. This activity used the Community-Based Participatory Action Research (CBPAR) method, which emphasises active collaboration between the service team and MSME partners. The process included participatory planning, collaborative action in the form of intensive training and mentoring, and joint evaluation. The results showed that all 10 MSME partners successfully adopted and used QRIS for daily transactions. The significant benefits included increased transaction efficiency, improved financial record-keeping, and a more modern business image. The main challenges identified were initial doubts about the technology and unstable internet connectivity, which were successfully mitigated through personalised mentoring based on trust. It was concluded that the CBPAR (Community-Based Participatory Action Research) method is a highly effective framework for implementing technological innovation in rural MSME communities because it not only addresses technical skill gaps but also builds crucial social capital such as trust and digital confidence.